تقييم كفاءة نظام الأراضي الرطبة لمعالجة مياه الصرف الصحي لأغراض الري في ظروف الساحل السوري - هيثم شاهين; علي حسيان (Tishreen University, 2018)
Most communities and villages in the Syrian coast are throwing their waste water in the valleys, streams and rivers, posing a major threat to water sources, especially the surface water source thus, we find that it is important to look for ways and mechanisms to address and manage these expenditures correspond. Where are the vegetation treatment plants(wetland), suitable for small-size and medium villages almost note that the German code permitted under the domain (1000-5000) people. we can use plants stations in Syria to address domestic sewage systems as near-normal low costs and easy maintenance as well as the efficiency of performance. Wetland systems are classified according, either due to fluid type: free water system (FWS), and sub-surface horizontal flow direction (SHF), and sub-surface vertical flow direction (SVF), either due to plant type: Floating plants, submerged plants, and rooted emergent plants. A wetland plant was designed using a reed plants with a vertical flow to treat Domestic waste water in Accar Region.Measurment and analyses were done through 12 months to evaluate the effluent water quality. Results were suitable for irrigation purposes according Syrian standards.     تقوم معظم التجمعات السكانية والقرى في الساحل السوري بإلقاء منصرفاتها في الوديان والمسيلات المائية ومجاري الأنهار، مما يشكل خطورة كبيرة على المصادر المائية وخصوصا" السطحية منها. من هنا، نجد أنه من الأهمية بمكان البحث عن طرق وآليات لمعالجة وإدارة تلك المنصرفات، حيث تعتبر محطات المعالجة بالنباتات (الأراضي الرطبة) مناسبة للقرى صغيرة الحجم إلى المتوسطة تقريباً علماً أنَّ الكود الألماني سمح بها ضمن المجال (1000 - 5000) نسمة. ویمكن استخدام محطات النباتات في سورية لمعالجة میاه المجاري المنزلیة باعتبارها منظومات شبه طبيعية قليلة التكاليف وسهلة الصيانة بالإضافة إلى كفاءة الأداء. يتم تصنيف محطات الأراضي الرطبة تبعاً لأنظمة تدفق المياه عبرها أو تبعا" للنباتات المستخدمة في المعالجة حيث تقسم حسب نظام تدفق المياه إلى أراضي رطبة ذات الجريان السطحي الحر ( FWS) وأراضي ذات الجريان التحت السطحي الأفقي(SHF) وأراضي ذات الجريان التحت السطحي الشاقولي(SVF) وأراضي ذات الجريانات المتنوعة (أفقي+ شاقولي..الخ) (Hybrid system) وتقسم حسب النباتات إلى محطات ذات نباتات طافية Floating plants) ) وذات نباتات مغمورة ( Submerged plants ) ومحطات نباتات ذات جذور مغمورة وسوق طافية (Rooted emergent plants). تمَّ تصميم منظومة طبيعية، باستخدام نبات القصب، ذات تدفق شاقولي لمعالجة مياه الصرف الصحي المنزلية بمنطقة سهل عكار في ريف طرطوس، ولقد أجريت الاختبارات لمدة عام كامل لتقييم جودة المياه الناتجة، لإعادة استخدامها لأغراض الري، حيث أعطت نتائج جيدة ملبية للمعايير المحلية السورية.